2018
DOI: 10.17268/sci.agropecu.2018.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Bread leaf enriched with extruded cake from sacha inchi (Plukenetia volubilis L.): Chemistry, rheology, texture and acceptability

Abstract: ResumenSe estudió la sustitución parcial de harina de trigo por torta extruida de sacha inchi (SI) en seis diferentes niveles para la elaboración de pan de molde. Evaluándose principalmente la composición química, propiedades reológicas, perfil de ácidos grasos, textura de la miga, color y evaluación sensorial. Se ha determinado que la incorporación de la torta extruida de SI en las formulaciones incrementó significativamente (p < 0,05) los niveles de cenizas, fibra, grasas y proteínas, asimismo disminuyó el c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The best rheological properties of farinography, amylography and extensography were obtained with the addition of SIOPC at 6.3%, reaching concentrations of protein, fiber, and α-linolenic acid of 10.3, 3.8 and 3.3%, respectively. Moreover, the sensory attributes of color, appearance, aroma, flavor, and texture of breads elaborated with this formulation were similar to those of the control samples [10] . Addition of SIOPC at higher levels (up to 25%) negatively affects the technological properties of the flour blends, batters, and breads, such as water absorption, extensibility, and texture.…”
Section: Applications Of Siopc As Functional Ingredient In Foodssupporting
confidence: 55%
See 1 more Smart Citation
“…The best rheological properties of farinography, amylography and extensography were obtained with the addition of SIOPC at 6.3%, reaching concentrations of protein, fiber, and α-linolenic acid of 10.3, 3.8 and 3.3%, respectively. Moreover, the sensory attributes of color, appearance, aroma, flavor, and texture of breads elaborated with this formulation were similar to those of the control samples [10] . Addition of SIOPC at higher levels (up to 25%) negatively affects the technological properties of the flour blends, batters, and breads, such as water absorption, extensibility, and texture.…”
Section: Applications Of Siopc As Functional Ingredient In Foodssupporting
confidence: 55%
“…The SIOPC contains important amounts of bioactive compounds, such as proteins, carbohydrates, minerals, and lipids, whose concentration varies, in addition to the intrinsic composition of the kernels, with the oil extraction' process efficiency. The SIOPC has been generally used in animal feeding [9] , as functional ingredient of various food products [10] , and as nonconventional source of proteins, protein isolates and hydrolysates [11] .…”
Section: Introductionmentioning
confidence: 99%
“…In Table 4, the texture analysis was represented by chewiness (mJ) and in all the formulations there were no significant differences (p<0.05) between them nor with respect to the control, which would indicate that the addition of flour of quinoa, cañihua and chia seeds in the added proportions do not increase the hardness of the crumb in a notorious way, so it can be stated that the energy for the loaves to disintegrate is not far from the control bread [20]. Generally, the addition of flours such as chestnut, flaxseed, sacha inchi increases the hardness of the crumb in bread formulations [29,30]. The addition of up to 20% of cañihua flour in wheat flour allows to maintain good properties with respect to texture and nutritional [31].…”
Section: Texture and Colormentioning
confidence: 99%
“…Švec et al [44] studied the amylographic properties of wheat flour, quinoa, cañihua, mixture between quinoa / wheat flour and cañihua / wheat flour in proportions of 10/90 and 20/80, determining that the maximum gelatinization temperature was found between 88 -94 ° C for all the samples. Rodriguez et al [30] found significant differences with respect to the maximum gelatinisation for wheat flour (1249 AU) with different levels of substitution of extruded sacha inchi cake (630 -986 AU). Recent studies indicate that one way to improve the rheological properties of breads based on wheat flour substituted with other protein sources such as lentil flour depends on the granulometry, since a coarse fraction can provide higher yields compared to unfractionated flour or to flours with finer fractions [9].…”
Section: Rheologymentioning
confidence: 99%
See 1 more Smart Citation